The Ontology of Crime and Punishment: Philosophical Foundations of Criminal Liability - Fitriani, Ni Putu; Wulandari, Ni Gusti Agung Ayu Mas Tri; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The concepts of crime and punishment in the philosophy of law are not only understood as positive legal constructs, but also as moral and ontological entities that reflect human views on responsibility and justice. An ontological understanding of crime and punishment is essential to affirming the moral foundation of the modern criminal law system. This study aims to examine the ontological nature of crime and punishment and to identify the philosophical foundations that shape the concept of criminal liability. This research is expected to bridge the relationship between morality, free will, and the legitimacy of criminal law. This study uses a qualitative approach with philosophical and hermeneutic analysis methods. The primary data sources come from classical moral philosophy literature and contemporary legal theories related to the concepts of moral and criminal responsibility. The analysis shows that crime is ontologically a violation of the moral order internalized in law. Punishment essentially functions as a moral restoration and affirmation of human rationality, which has freedom of action. Criminal responsibility is only meaningful if the perpetrator is deemed to have moral awareness and the capacity for free will. This study concludes that the philosophical foundation of criminal responsibility lies in the ontological understanding of humans as autonomous moral subjects. Thus, criminal justice is not only legal-formal in nature, but also stems from rational ethics and universal moral values.